Bone mass and biochemical markers of bone turnover in children and adolescents with chronic immune thrombocytopenia: Relation to corticosteroid therapy and vitamin D receptor gene polymorphisms. (June 2013) - Tantawy, Azza A. G.; El Bostany, Eman A.; Matter, Randa M.; El Ghoroury, Eman A.; Ragab, Shadia; El Sherif, Nayera H. K.
<x xml:space="preserve">Abstract</x> Optional drug therapy in refractory chronic immune thrombocytopenia (ITP) includes standard oral, pulsed high-dose steroid therapy, intravenous gamma globulin, anti-D, and immunosuppressive therapy or thrombopoietin receptor agonists. This work aimed to study the bone mass in children and adolescents with chronic ITP in relation to biochemical markers of bone turnover, cumulative steroid therapy, and the possible modulating effect of vitamin D receptor (VDR) gene polymorphisms. Thirty-six children and adolescents with chronic ITP were recruited from the Hematology Clinic, Children's Hospital, Ain Shams University and the Hematology Clinic of the National Research Centre in Egypt and compared with 43 healthy age- and sex-matched controls. The total cumulative dose of steroids was calculated. Bone markers (serum osteocalcin (OC) and propeptide I precollagen (PICP) and urinary deoxypyridinoline (DPD) excretion), analysis of VDR gene distribution, and dual energy X-ray absorptiometry at lumbar and hip regions were performed for patients and controls. Compared to controls, chronic ITP patients had higher body mass index (BMI) and lower height for age standard deviation score (SDS). Chronic ITP patients had lower levels of OC and C-terminal propeptide of type I procollagen (PICP) and higher urinary DPD excretion, and bone mineral density (BMD) was significantly lower for both spine and hip z-score (<0.001). BMD was inversely correlated with urinary DPD excretion, age, BMI, and cumulative steroid dose. There was significant negative correlation between cumulative oral steroid dose and BMD (r = −0.4, P = 0.01 and r = −0.45, p = 0.001 for spine and hip z-scores, respectively), but the correlation was non-significant in relation to cumulative pulsed steroid therapy. FokI polymorphism was significantly related to BMD for both spine and hip z-score (p = 0.015 and p = 0.008, respectively), but there was no relation between BMD and Bsm1 polymorphism. FokI gene polymorphism may be one of the contributing factors in bone loss in patients on chronic steroid therapy. High cumulative doses of corticosteroids increased bone resorption in young chronic ITP patients. Longitudinal studies are needed to confirm the effect of different steroid protocols on bone turnover. Protocols of therapy of chronic ITP should restrict corticosteroid use in growing children and favor alternative less harmful therapies.